NordiQC Assessments of CD117 Immunoassays. Issue 2 (February 2019) - Røge, Rasmus; Bzorek, Michael; Nielsen, Ole; Vyberg, Mogens
Abstract : This paper is the number 5 in a series developed through a partnership between ISIMM and NordiQC for the purpose of reporting research assessing the performance characteristics of immunoassays in an external proficiency-testing program.